The Feasibility of Outdoor Psychology Sessions in an Adult Mental Health Inpatient Rehabilitation Unit: Service User and Psychologist Perspectives - James, Gail; Kidd, Katherine; Cooley, Sam J.; Fenton, Kelly (Frontiers in Psychology, 2021)
Few studies have explored outdoor therapy when facilitated by clinical psychologists within an inpatient mental health service. In the present study, outdoor psychology sessions were introduced after service users (SUs) expressed a desire to return to face-to-face working during the COVID-19 pandemic. This study aimed to explore SUs’ and clinical psychologists’ perspectives on the feasibility of conducting outdoor therapy within the service. A mixed-method approach was underpinned by critical realist philosophy. Three psychologists maintained reflective diaries following outdoor therapy sessions with 16 SUs. A subsample of 14 SUs completed scales measuring therapeutic alliance and comfort during outdoor sessions. A subsample of eight SUs participated in semi-structured interviews. Data was analysed using descriptive statistics and thematic analysis. Quantitative and qualitative data demonstrated high SU satisfaction with therapeutic alliance and comfort outdoors. Six themes were identified: utilising a person-centred approach; the value of multi-disciplinary team support; enhancing therapeutic engagement; the benefits of time away from the ward; managing confidentiality; physical health and safety. This feasibility study demonstrated the introduction of outdoor psychology sessions within an inpatient mental health service to be a viable response to COVID-19. The findings suggest outdoor therapy can be an effective and safe mode of therapy, and can offset the challenges of indoor working, providing certain risk factors are considered and managed. The limitations of this study and implications for clinical practice are discussed. Further research is now required to support future integration into clinical practice.